Risk preferences under heterogeneous environmental risk - Roland Olbrich; Stefan Baumgärtner; Martin F. Quaas; Andreas Haensler (Verein für Socialpolitik, 2010)
We elicit risk preferences and their determinants through a survey and field experiments for cattle farmers in Namibia who are subject to heterogeneous environmental risk. Survey data is complemented with precipitation data simulated by a climate model to analyze the relationship between risk preferences and individual precipitation risk. We find that risk aversion is inversely related to precipitation risk. When considering individual opportunity sets we find that background risk is not heterogeneous and that liquidity constraints do not influence risk aversion. The observed pattern in behavior towards risk and the interaction with environmental risk can thus be attributed to preferences.
Keywords: D81; Q12; Q57; 330; risk preferences; environmental risk; experimental elicitation